Twisted ladder-like donor-acceptor polymers as electrode materials for flexible electrochromic supercapacitors. (10th February 2020) - Sun, Ying; Zhao, Xuan; Zhu, Guanqun; Li, Man; Zhang, Xueqin; Yang, Hong; Lin, Baoping
Abstract: Three ladder-like donor-acceptor (D-A) polymers PI-IDT, PI-BT, PI-DPP containing twisted spirobifluorene unit were synthesized and applied as electrochromic supercapacitor electrodes. By using density functional theory (DFT), we found that the polymer exhibited a distinct HOMO/LUMO wave function distribution when the linker moiety was electron-donors and electron-acceptors, respectively. Due to the introduction of the twisted unit, PI-IDT based on electron donor indacenodithiophene (IDT) unit as the linker moiety expressed a completely separated HOMO/LUMO wave function，and possessed independent p/n-dopable redox properties. With the separation of p-doped site and n-doped site, PI-IDT exhibited excellent performances in p-doping, n-doping and full cyclic scan including p-doping and n-doping processes. The area specific capacitance could reach 6.2 mF cm −2 during p-doping process, and 2.4 mF cm −2 during n-doping process. While the other two polymers PI-BT, PI-DPP based on the benzodithiazole (BT) and diketopyrrolopyrrole (DPP) as the linking unit, respectively, were characterized as that the p-doped sites and n-doped sites were located on one moiety, showing limited capacitance and poor stability. Besides, the selection of different linking units also directly affected the electrode-electrolyte interface contact, film-forming properties, electrochromic and electrochemical properties of the polymer. In addition, PI-IDT had a rich color change (orange, green, blue) and excellent coloring efficiency (155 cm 2  C −1 ). The asymmetric supercapacitor PI-IDT//W0.71 Mo0.21 O3-x with PI-IDT as anode material showed discoloration from orange to blue, and delivered an energy density of 3.89 W h kg −1 . Graphical abstract: Image 1